Magnesium Alloys - Selected Issue 2018
DOI: 10.5772/intechopen.80291
|View full text |Cite
|
Sign up to set email alerts
|

Microstructure and Properties of Casting Magnesium Alloys Designed to Work in Elevated Temperature

Abstract: Magnesium alloys are widely used in aerospace and automotive industry due to their low density, good mechanical properties, and good castability. Their main disadvantage is low maximum working temperature (about 120°C for Mg-Al alloys). This led to the development of Mg-Al-RE or Mg-RE-Zr alloys, which can work up to 250°C. The chapter will relate to the sand cast and high pressure die cast magnesium alloys. Material for the research consisted of six magnesium casting alloys: AE44, AJ62, WE54, EV31A, and for co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 15 publications
(18 reference statements)
0
4
0
Order By: Relevance
“…Throughout literature, the hardness testing conditions, the ageing temperature and ageing time ranges, as well as the initial state of the alloy before testing vary greatly. Nevertheless, the general consensus lies in the good age hardening response of WE series magnesium alloys below 300 °C, as well as the fact that lower ageing temperatures generally lead to increased peak ageing hardness values (Mengucci et al, 2008;Kandalam et al, 2015;Huang, 2017;Kang et al, 2017;Kiełbus et al, 2018). In addition, it has been reported that double-step ageing treatments can bring additional benefits for WE alloy performance (Riontino et al, 2008).…”
Section: Propertiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Throughout literature, the hardness testing conditions, the ageing temperature and ageing time ranges, as well as the initial state of the alloy before testing vary greatly. Nevertheless, the general consensus lies in the good age hardening response of WE series magnesium alloys below 300 °C, as well as the fact that lower ageing temperatures generally lead to increased peak ageing hardness values (Mengucci et al, 2008;Kandalam et al, 2015;Huang, 2017;Kang et al, 2017;Kiełbus et al, 2018). In addition, it has been reported that double-step ageing treatments can bring additional benefits for WE alloy performance (Riontino et al, 2008).…”
Section: Propertiesmentioning
confidence: 99%
“…AZ31, for example, exhibits a weak strengthening effect, displaying a nearly constant hardness over ageing time (Xu et al, 2018). Furthermore, artificial ageing processes have also a more positive effect on the mechanical properties of WE series magnesium alloys than on EV31 (Kiełbus et al, 2018).…”
Section: Propertiesmentioning
confidence: 99%
“…Depending on the aging temperature and time, the precipitating sequence in WE alloys has been reported to involve the formation of phases β″, β′, and β. The equilibrium β phase is isomorphic to the Mg 5 Gd phase and is identified as a Mg 14 Nd 2 Y phase [13].…”
Section: Cast Mg Alloysmentioning
confidence: 99%
“…The β-phase distributed continuously and discontinuously along the grain boundary and in the grain interiors in the microstructure of an AZ91 Mg alloy causes substantial grain boundary sliding at elevated temperatures. Also, low melting point and incoherency with Mg matrix (HCP lattice) of a β-Mg 17 Al 12 (cubic lattice) phase suffer severe cracking and cavity formation, resulting in lower creep resistance of AZ91 Mg alloy [19][20][21]. A. Srinivasan et al [19] reported the much lower creep life for AZ91 Mg alloy at the stress of 50 MPa and the temperature of 150 o C compared to AZ91 Mg alloy with Sb and Si addition.…”
Section: Introductionmentioning
confidence: 99%